(untitled) (Tamaddun, 2025)
In the modern digital age, students’ ways of communicating and developing character are deeply shaped by both their surrounding environments and their engagement with technology. This study explores how environmental conditions and digital technology together affect positive communication and character formation among university students, viewed through a neurobehavioral lens. Using a qualitative method, 35 students were purposively chosen and involved through online questionnaires and observation. The results show that supportive families, peers, and campus environments strengthen openness, empathy, and respectful communication (94–97%), while technology enhances communication efficiency (97%) but can also lead to emotional strain (55%). From a neurobehavioral perspective, both environmental and digital factors influence how students regulate emotions and make decisions. The study concludes that balanced interaction between social support and mindful technology use promotes empathy, moral awareness, and emotional stability, key components of strong character and positive communication in higher education.